The effect of anaerobic effort on the level of triiodothyronine in advanced basketball players - Ashour, Mohammed; Abdul Reda, Firas (Journal of Physical Education, 2025)
To perform any physical effort, any body needs a lot of energy sources, including carbohydrates, fats, or chemical sources that vary in rates depending on the nature of the activity performed. Therefore, hormones play an important role in regulating the body’s functions during physical effort. The hormone triiodothyronine is one of the hormones that work to increase the level of activities of the necessary body systems The problem of the research lies in identifying more information about the effect of anaerobic effort on the hormone triiodothyronine in some basketball players in order to benefit from it and take it into consideration during the training planning process. The research aims to identify the effect of anaerobic effort on the hormone triiodothyronine in some advanced basketball players. The researchers used the descriptive approach to suit the nature of the problem, and the research sample was the advanced basketball players of the Popular Mobilization Club. The researchers concluded that the hormone triiodothyronine (T3) is decisive in its effect during rest or after effort, which indicates the important effect of exercise, as well as the effect of anaerobic effort on the secretion of Triiodothyronine hormone: Researchers recommended adopting triiodothyronine measurement as an indicator for selecting players as it is a clear indication of sports training adaptations.